The company of others: generating knowhow in later life. Issue 5 (2nd September 2016) - Kimberley, Helen; Golding, Barry; Simons, Bonnie
Abstract: This paper explores some important aspects of the generation of practical knowledge through later life. It is about the relationship between knowledge generation, agency and capability, developed informally through the life experiences in and through the Company of Others. It emphasises how the everyday processes of socialisation create invaluable opportunities to know how to navigate the diverse and complex changes thrown up in the journey through later life. It asks where and how knowhow is generated after workforce participation ceases and pays particular attention to 'third places', opportunities in the community that enable social connections beyond the first and second places, home and work, respectively. The empirical and theoretical data come from two main Australian sources amplified by new international research in cognate fields. The first is a study about Generating knowhow in later life . The second derives from insights from research for a book into the origins and nature of the now international Men's Shed Movement .